2009
DOI: 10.1097/mpa.0b013e3181a488a0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of the Measurements of Serum Matrix Metalloproteinase-9 and Its Inhibitor (Tissue Inhibitor of Metalloproteinase-1) in Patients With Pancreatic Cancer

Abstract: These findings indicate a potential clinical significance of serum TIMP-1 and MMP-9 measurements in the diagnosis and prognosis of patients with PC, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 17 publications
5
38
0
1
Order By: Relevance
“…In patients with PDAC, both ICAM-1 and TIMP-1 levels were significantly higher than in healthy controls ( Fig. 1a and b), as previously reported [3][4][5][6][7][8][9][10]. PDAC patients with biliary obstruction (bilirubin levels > 20 μmol/L) had significantly higher levels of both ICAM-1 (p < 0.001) and TIMP-1 (p = 0.024) than PDAC patients without biliary obstruction (bilirubin levels < 20 μmol/L).…”
Section: Biological Significancesupporting
confidence: 80%
See 1 more Smart Citation
“…In patients with PDAC, both ICAM-1 and TIMP-1 levels were significantly higher than in healthy controls ( Fig. 1a and b), as previously reported [3][4][5][6][7][8][9][10]. PDAC patients with biliary obstruction (bilirubin levels > 20 μmol/L) had significantly higher levels of both ICAM-1 (p < 0.001) and TIMP-1 (p = 0.024) than PDAC patients without biliary obstruction (bilirubin levels < 20 μmol/L).…”
Section: Biological Significancesupporting
confidence: 80%
“…In addition, the sensitivity of some markers for the detection of PDAC over healthy controls was recently shown to be considerably higher for PDAC patients in the presence of obstructive jaundice compared to PDAC patients in the absence of obstructive jaundice [2]. Two serum proteins, identified in several studies as potential diagnostic biomarkers due to their upregulation in PDAC, are ICAM-1 [3][4][5][6] and TIMP-1 [3][4][5][7][8][9][10]. In order to determine whether ICAM-1 and TIMP-1 levels are affected by biliary obstruction we compared samples (Liverpool cohort) taken at diagnosis from patients with PDAC (in the presence or absence of jaundice), chronic pancreatitis, benign biliary obstruction or from healthy controls.…”
Section: Biological Significancementioning
confidence: 98%
“…Studies in several cancers have correlated higher levels of MMP-9 and VEGF with tumor stage and high metastatic potential. [27][28][29][30] Our analyses reported here have found that MMP-9 and VEGF were found in 100% of invasive PDA lesions, of which 66% were smokers. This is the first report to examine the relationship between tumor MMP-9 and VEGF and the status of smoking in PDA patients.…”
Section: Discussionmentioning
confidence: 84%
“…Although several studies have shown that MMPs and VEGF are overexpressed in PDA and play important roles in its progression, [27][28][29][30] and that their overexpression is regarded as a prognostic factor in PDA, 28,30 very few have investigated their relationship to smoking and the upstream factors involved in their regulation in PDA cells. In this OPNc, and GAPDH, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there are 11 recent studies on CEA which can be detected at low levels in fetal and normal adult tissue while high serum levels indicate presence of pancreatic cancer. The main problem of this biomarker is its low sensitivity of 25-56% at a high specificity of 82-100% for discriminating carcinoma from controls (Duraker et al 2007;Ehmann et al 2007;Gansauge et al 1996;Groblewska et al 2007;Liao et al 2009;Mroczko et al 2009;Ni et al 2005;Pasanen et al 1994;Zhao and Zhang 2008) (Table 1B). The best performance was reported by Ehmann et al (2007) on 96 carcinomas and 96 controls with 56% sensitivity and 82% specificity.…”
Section: Group B: Carcinoembryonic Antigenmentioning
confidence: 96%